Genetic control of stem elongation in common bean and the influence of age and flowering time - Chantelle J. Beagley; Jacqueline K. Vander Schoor; Jakob B. Butler; James L. Weller (Theoretical and Applied Genetics, 2025)
Key message Genetic analysis of stem elongation in common bean identified loci acting at different developmental stages and reveals interactions with flowering time. Abstract Stem internode elongation is a major determinant of growth habit and plant height, and is often responsive to environmental signals, making it an integral component of plant architecture and a core characteristic targeted for crop improvement. More effective exploitation of stem elongation requires increased understanding of not only major determinants, but also of more subtle, specific influences as breeders seek to further refine adaptation to local growing environments. Common bean is a globally important legume crop and exhibits extensive variation in stem elongation, but there is little knowledge about the underlying genetic control. To better understand this trait, we performed a comprehensive genetic analysis in a wide F 2 cross between wild and domesticated bean. By conducting quantitative trait locus (QTL) analyses of the length of individual internodes, we discovered four main genomic regions influencing internode length at different stages of development. Of these, one demonstrated strong association with the two known flowering genes Fin and Ppd on chromosome 1, while two other regions were validated in subsequent F 3 and F 4 generations and were demonstrated to be independent of flowering time. These results highlight the complex dynamic nature and potential pleiotropic interactions of elongation genes throughout development, and indicate new avenues of inquiry towards improving crop adaptation to specific environments.